Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume - IV General Areas Government of Assam - Planning Commission (Planning Commission, 1985)
In Schedule Caste areas under Schedule Caste component plan, out of the approved 6th Plan outlay of Rs. 156 lakhs, Rs. 84.19 lakhs have been utilised upto 3/83. Expenditure for 1983-84 is Rs. 35.34 lakhs and for 1984-85 anticipated expenditure will be Rs. 40.00 lakhs, making a total of Rs. 159.53 lakhs. About 119 Kms. of Minimum Needs Programme rural roads and about 45 Kms. of OMNP roads are expected to be completed in Schedule Caste areas by the end of 6th Plan.
Planning and Development Department, Government of Assam